Bacterial and archaeal spatial distribution and its environmental drivers in an extremely haloalkaline soil at the landscape scale - Martínez-Olivas, Martha Adriana; Jiménez-Bueno, Norma G.; Hernández-García, Juan Alfredo; Fusaro, Carmine; Luna-Guido, Marco; Navarro-Noya, Yendi E.; Dendooven, Luc (PeerJ, 2019)
Background A great number of studies have shown that the distribution of microorganisms in the soil is not random, but that their abundance changes along environmental gradients (spatial patterns). The present study examined the spatial variability of the physicochemical characteristics of an extreme alkaline saline soil and how they controlled the archaeal and bacterial communities so as to determine the main spatial community drivers. Methods The archaeal and bacterial community structure, and soil characteristics were determined at 13 points along a 211 m transect in the former lake Texcoco. Geostatistical techniques were used to describe spatial patterns of the microbial community and soil characteristics and determine soil properties that defined the prokaryotic community structure. Results A high variability in electrolytic conductivity (EC) and water content (WC) was found. Euryarchaeota dominated Archaea, except when the EC was low. Proteobacteria, Bacteroidetes and Actinobacteria were the dominant bacterial phyla independent of large variations in certain soil characteristics. Multivariate analysis showed that soil WC affected the archaeal community structure and a geostatistical analysis found that variation in the relative abundance of Euryarchaeota was controlled by EC. The bacterial alpha diversity was less controlled by soil characteristics at the scale of this study than the archaeal alpha diversity. Discussion Results indicated that WC and EC played a major role in driving the microbial communities distribution and scale and sampling strategies were important to define spatial patterns.
Keywords: Soil maps; Cross validation; Soil properties; Biogeography; Spatial patterns; Prediction; Geostatistics; Ordinary kriging